Suitability study of local bush bean cultivars intercropped with hybrid maize under different planting system in hilly areas (Bangladesh Journal of Agricultural Research, 2015)
An intercropping experiment was conducted on hill valley at Hill Agricultural Research Station, Ramgarh and Kharachari during two consecutive rabi seasons of 2012-13 and 2013-14 to select suitable local bush bean cultivar for intercropping with hybrid maize in hilly areas of Bangladesh. Seven intercropping treatments viz., T1 = Normal maize spacing (75 cm × 25 cm) + 2 rows black seeded bush bean,T2 = Normal maize spacing (75 cm × 25 cm) + 2 rows pink seeded bush bean,T3 = Maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows black seeded bush bean,T4 = Maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean, T5 = Maize wider spacing (100 cm × 50 cm) with 2 plants/hill + 3 rows black seeded bush bean, T6 = Maize wider spacing (100 cm × 50 cm) with 2 plants/hill + 3 rows pink seeded bush bean and T7 = Sole maize spacing (75 cm × 25 cm) were used. Sole hybrid maize produced the highest grain yield at both the locations. Bush bean cultivars in intercropped situation depressed hybrid maize yields by 7.15-37.29% at Ramgarh and 2.56-37.51% at Khagrachari compared to sole hybrid maize. The highest maize equivalent yield of 23.10 t/ha at Ramgarh and 24.08 t/ha at Khagrachari was recorded in maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean combination (T4). The same treatment also showed the highest gross return (Tk 277200/ha at Ramgarh and Tk 288960/ha at Khagrachari), gross margin (Tk 180050/ha at Ramgarh and Tk 191810/ha at Khagrachari) and benefit cost ratio (2.85 at Ramgarh and 2.97 at Khagrachari). The result revealed that maize wider spacing (100 cm × 25 cm) with 1 plant/hill + 3 rows pink seeded bush bean could be suitable and economically profitable for hybrid maize and bush bean intercropping in hill valleys of Bangladesh.Bangladesh J. Agril. Res. 40(2): 325-332 June 2015